International Awareness Through Intercultural Interviews - Reitzel, Armeda; Sims, Judy (Speech Communication Association of Puerto Rico, 1985)
This paper discusses the use of an intercultural radio interview project as a means to making both intercultural communication students and the local community more aware and appreciative of their own cultures and other cultures in the “global village.” The project involved students from intercultural communication classes at Humboldt State University and the university’s public radio station, KHSU, 90.5 FM. The intercultural interviews were developed and conducted by the intercultural communication students; the radio station staff edited and aired the final productions. The taped productions were aired as a public affairs segment of KHSU’s “International Folk Show.” Objectives of the project included: (1) heightening student and community awareness of diverse international viewpoints and ways of thinking; (2) developing students’ communication skills (interpersonal and intrapersonal); and (3) focusing the intercultural communication students’ interests and efforts on a major culminating communication activity. This paper describes the activities involved in preparing, developing, producing, and promoting the intercultural radio interviews; summarizes student and audience reactions to the interviews; and provides specific suggestions for the use of the radio interview activity. Through the intercultural communication experiences of the radio interviews, the students and the listening community were presented with opportunities to learn and become more aware of international perspectives, as well as ideas and concepts from cultures other than their own; culture learning potentially occurred for all involved. Informal interpersonal skills were practiced and sharpened; international students developed their verbal communication skills in U.S. American English, and U.S. American students learned to feel less anxious from language and perception barriers. Intrapersonal communication skills also were enhanced; students became more aware of their own verbal and nonverbal cues as they tried to communicate with individuals from cultural and linguistic backgrounds different from their own. The interview project, which served to focus the students’ interests and efforts on a major culminating communication activity, allowed students to integrate book learning with experiential learning. The assignment required students to think critically about communication through a series of steps including conducting, producing, and listening to their interviews; journaling about their impressions of the experience, writing a summary report, and delivering an oral presentation. Students, community members, and educators can all become aware of the views and values of people from different cultures through intercultural radio interviews. Exploring channels of communication through intercultural radio interviews can be a positive and effective exercise in cultivating communication skills and culture learning. (Contains References: Seven sources).
Although this paper was accepted for presentation at the SCA of Puerto Rico Convention, the author scheduled to present was not able to attend the meeting due to extenuating circumstances. However, a related paper authored by Reitzel & Sims (1985, April 19-21) and based on the same intercultural interview radio project, was presented at the 16th California Association of Teachers of English to Speakers of Other Languages (CATESOL) conference, San Diego, CA. The CATESOL paper was titled, "Tuning into Internationalism through Radio.”
Keywords: Cultivating communication skills; Intercultural communication; Intercultural communication students; Culture learning; Experiential learning; Intercultural radio interviews; International students; Interpersonal communication skills; Intrapersonal communication skills; Language and perception barriers; Verbal communication skills